(untitled) (Jóvenes en la Ciencia, 2024)
Dry eye syndrome is a common condition and is estimated to affect more than 7 million people over the age of 40. In the world, reports indicate that 10 to 20% of the general population is affected. The use of medications, climate and environmental changes, the increase in the use of air conditioning, as well as the prolonged use of televisions have induced the exacerbation of symptoms, causing a reduction in ocular humidity. OBJECTIVE: To know the level of incidence of dry eye syndrome associated with the night shift of nursing staff at the Silao General Hospital. A descriptive, observational, cross-sectional and retrolective study was carried out. Information was collected through a survey of 25 nurses using an OSDI (Ocular Surface Disease Index) questionnaire, which is a specific questionnaire to measure the severity of ocular surface disease, where questions related to dry eye symptoms and/or factors were asked. associated and whether or not they present other types of pathologies in the night shift nursing staff. It was shown that 88% of the surveyed population showed some symptoms related to dry eye syndrome, however, 62% have some ocular disorder that affects the presence of the symptoms, coupled with 60% who spend more than 4 hours in front of the eye. to an electronic screen, being external factors for the appearance of dry eye syndrome. These results suggest that the incidence of dry eye associated with the night shift in nursing staff is high, with more factors related to the environment generating the incidence of this pathology.